Data from: The density and spatial arrangement of the invasive oyster Crassostrea gigas determines its impact on settlement of native oyster larvae - Wilkie, Emma M.; Bishop, Melanie J.; O'Connor, Wayne A. (Dryad, 2014)
Understanding how the density and spatial arrangement of invaders is critical to developing management strategies of pest species. The Pacific oyster, Crassostrea gigas, has been translocated around the world for aquaculture and in many instances has established wild populations. Relative to other species of bivalve, it displays rapid suspension feeding, which may cause mortality of pelagic invertebrate larvae. We compared the effect on settlement of Sydney rock oyster, Saccostrea glomerata, larvae of manipulating the spatial arrangement and density of native S. glomerata, and non-native C. gigas. We hypothesized that while manipulations of dead oysters would reveal the same positive relationship between attachment surface area and S. glomerata settlement between the two species, manipulations of live oysters would reveal differing density-dependent effects between the native and non-native oyster. In the field, whether oysters were live or dead, more larvae settled on C. gigas than S. glomerata when substrate was arranged in monospecific clumps. When, however, the two species were interspersed, there were no differences in larval settlement between them. By contrast, in aquaria simulating a higher effective oyster density, more larvae settled on live S. glomerata than C. gigas. When C. gigas was prevented from suspension feeding, settlement of larvae on C. gigas was enhanced. By contrast, settlement was similar between the two species when dead. While the presently low densities of the invasive oyster C. gigas may enhance S. glomerata larval settlement in east Australian estuaries, future increases in densities could produce negative impacts on native oyster settlement. Synthesis and applications: Our study has shown that both the spatial arrangement and density of invaders can influence their impact. Hence, management strategies aimed at preventing invasive populations reaching damaging sizes should not only consider the threshold density at which impacts exceed some acceptable limit, but also how patch ...